(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Müllerian anomalies are congenital malformations of the female genital tract resulting from abnormal development, fusion, or resorption of the paramesonephric ducts. Though uncommon, they are clinically important because they are associated with malpresentation, preterm delivery, operative intervention, and adverse perinatal outcomes. Evaluating their impact on pregnancy and delivery is essential for improving antenatal surveillance and obstetric management. Aim & Objective: To evaluate the spectrum of Müllerian anomalies and their impact on delivery outcome, and to correlate anomaly type with obstetric complications, fetal presentation, preterm birth, low birth weight, and maternal and neonatal outcome. Materials & Methods: This retrospective case series was conducted at KIMS, Koppal, from March 2024 to March 2025 among 10 pregnant women with Müllerian anomalies diagnosed before pregnancy, antenatally, or intraoperatively. Pregnancies beyond 28 weeks were evaluated for demographic profile, anomaly type, clinical presentation, delivery details, intraoperative findings, and maternal and neonatal outcomes. Results: Equal proportions of women belonged to 20 to 24 years and 25 to 29 years age groups. Multigravida constituted 70%, previous abortion was noted in 40%, and hypertensive disorders in 30%. Arcuate uterus was the commonest anomaly (50%), followed by bicornuate uterus (20%). Breech/podalic presentation occurred in 70%, while 70% delivered after 37 weeks. Caesarean section was performed in all cases. Postpartum hemorrhage occurred in 30%, and blood transfusion was required in 10%. Low birth weight was seen in 30%, SNCU admission in 50%, and neonatal survival was 100%. Conclusion: Müllerian anomalies significantly influence delivery outcome by increasing malpresentation, operative delivery, and selected maternal and neonatal risks. Early diagnosis and careful obstetric management can improve fetomaternal outcome.